PORTAL APLIKASI KAJIAN ILMU KEISLAMAN BERBASIS ANDROID PADA MAJLIS TAKLIM DKM NURUL HUDA - Buhori Muslim; Eva Susilawati; Emil Herdiana (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Cianjur as a City of Santri, of course, there are many Islamic studies carried out in langgar, mosque, surau, Islamic boarding school or school, currently these studies are only local and can only be heard by people around mosques, Information Technology and Information Systems (SITI) has been found to be the most effective disseminator of information and of course it can also be an alternative in Islamic religious studies so that studies can be carried out by anyone anywhere. In making this portal application the study of Islamic science is the system development method used, namely waterfalls, the waterfall application in this study is the most suitable because the system is built with great systematic and good accuracy so that the resulting system is good and in accordance with the needs of users from application. This application that is built requires an analysis of computer hardware and android-based smartphones, where the creation begins with the design, the design is modeled with UML and the Java programming language, android and database using firebase. The results of this study are the application portal for Islamic studies that is most suitable for Android smartphone users.